Agriculture and the nitrogen cycle : assessing the impacts of fertilizer use on food production and the environment - Mosier, Arvin; Syers, John K. (John Keith); Freney, J. R. (John Raymond) (SCOPE report, 2004)
Annotation "Agriculture an dthe Nitrogen Cycle provides a unique, up-to-date assessment of the role of nitrogen fertilizer in the nitrogen cycle. In it, the authors emphasize the need to maintain food and fiber production while minimizing environmental impacts where fertilizer is abundant, and the need to enhance fertilizer utilization in systems where nitrogen is limited. The book is derived from a workshop held by the Scientific Committee on Problems of the Environment (SCOPE) that brought together the world's leading scientists to examine the nitrogen cycle and related problems."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved